2000
DOI: 10.1177/10454411000110030401
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Resin-Modified Filling Materials

Abstract: Increasing numbers of resin-based dental restorations have been placed over the past decade. During this same period, the public interest in the local and especially systemic adverse effects caused by dental materials has increased significantly It has been found that each resin-based material releases several components into the oral environment. In particular, the comonomer, triethyleneglycol di-methacrylate (TEGDMA), and the 'hydrophilic' monomer, 2-hydroxy-ethyl-methacrylate (HEMA), are leached out from va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
275
0
20

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 360 publications
(300 citation statements)
references
References 137 publications
5
275
0
20
Order By: Relevance
“…Primary cells represent clinical conditions better, but are diversified and have lower viability. 20 TheISO 10993 standard, standardizing in vitro studies, supports the use of permanent cell lines. 2,4,12 In our study, we used a standard human gingiva fibroblast line; and to reproduce conditions similar to clinical, we placed samples of materials on a semi-permeable membrane of inserts.…”
Section: Discussionmentioning
confidence: 99%
“…Primary cells represent clinical conditions better, but are diversified and have lower viability. 20 TheISO 10993 standard, standardizing in vitro studies, supports the use of permanent cell lines. 2,4,12 In our study, we used a standard human gingiva fibroblast line; and to reproduce conditions similar to clinical, we placed samples of materials on a semi-permeable membrane of inserts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that each resin-based material releases several components into the oral environment. In particular, the hydrophilic monomer, 2-hydroxyethylmethacrylate (HEMA), is leached out from various composite resins and adhesive materials in considerable amounts during the first 24 h after polymerization (Geurtsen 2000). Moreover, HEMA, together with tetraethylenglycol dimethacrylate (TEG-DMA), is able to diffuse through dentine into the pulp space at significantly high concentrations in the millimolar range (Bakopoulou et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Resinbased dental composites may release components from the resinous matrix, which could be initially due to partial polymerization, and/or later due to degradation processes over time [1][2][3][4] . These released components come into contact with oral tissues and may have various drawbacks like urticarial and mucosal reactions 5 , development of allergy and hypersensitivity reactions in patients 6 , modifications of gingival fibroblasts morphology and reduction on type I collagen protein 7 , immunosuppression or immunostimulation on mitogen-driven proliferation of purified T-lymphocytes and spleen cells 8 and DNA damage in primary human gingival fibroblasts, which underlines their genotoxic potential 9 .…”
Section: Introductionmentioning
confidence: 99%